PENGARUH PENDAPATAN ASLI DAERAH (PAD) DAN DANA ALOKASI UMUM (DAU) TERHADAP BELANJA MODAL PROVINSI KALIMANTAN TIMUR - DIAN ANGGREANI (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2016)
Capital Expenditure relationship that can be viewed from the General Allocation Fund note that revenue actually are the mainstay for the region to support the governance and financing for development. But the reception area of the elements of the original income alone is not able to meet the needs of the area especially with the addition of local authorities will clearly require additional funding for the region so that the region still needs help or funds from the center. Help centers are usually called the General Allocation Fund. The purpose of this study was to examine the effect of revenue and the General Allocation Fund to the Capital Expenditure East Kalimantan province by using multiple linear regression analysis and hypothesis test t test (partial). Based on the results of hypothesis testing by t test (partial) note that the original income has a positive influence and significant impact on Capital Expenditure by t test results of 3.512 and α 0.002. Furthermore, the partial general allocation funds do not have a negative influence and significant to the Capital Expenditure by t test of -0.235 and α 0.817.Keywords: Revenue, General Allocation Fund, Capital Expenditure